The Relationship Between Perceived Leadership Behaviours and Job Satisfaction of Middle Managers in Tenaga Nasional Berhad (TNB) Malaysia - Marimuthu, Jaganathan (1998)
The problem investigated in this research is whether perceived leadership behaviours of the superiors namely, initiating structure and consideration, will have an impact on the job satisfaction of the middle managers of Tenaga Nasional Berhad (TNB). The survey instrument used was a questionnaire comprising three sections. The first section sought respondents' personal information while the second section, a modified version of the Leader Behavior Description Questionnaire, measured managers' perception of the leadership behaviours of their superiors. The final section, a modified version of the Minnesota Satisfaction Questionnaire, was aimed at gauging the level of job satisfaction of middle managers of TNB. The questionnaire was then distributed to a randomly selected sample of 350 middle managers of TNB. One hundred and twelve of them responded but only 106 of the questionnaires were complete. Descriptive and inferential statistical procedures, namely, frequencies, t-test, one-way ANOVA, correlation and multiple regression were used to analyze the data.